Work Accident Risk Analysis in Building Renovation Project at PT. XYZ Using the FMEA Method: Analisis Risiko Kecelakaan Kerja Pada Proyek Renovasi Bangunan di PT XYZ Menggunakan Metode FMEA - Rizky Amalia Khusna; Minto Waluyo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Construction projects naturally involve a high risk of work-related accidents, with potentially serious consequences if they occur. This is especially relevant in developing countries, where the risk of work-related accidents tends to be higher. In general, risk is defined as a situation that has the potential to have a detrimental impact on an individual or organization. Managing occupational safety and health (OHS) risks becomes very important. The Failure Mode and Effect Analysis (FMEA) method is used to identify risks by calculating the Risk Priority Number (RPN) value. Based on the results of the analysis of work-related accident risks in the building renovation project at PT XYZ, the highest RPN value was obtained, namely 251.6, in the wall and ceiling painting process. The risks identified include eye irritation and poisoning due to paint vapors during the painting process. A fishbone diagram was prepared to identify the main factors that could increase the potential for work-related accidents. The results of this analysis were used to design work-related accident risk control measures in the renovation project at PT XYZ.